Research on Mechanized Plasma Gouging of Weldable Construction Steels - Olah Arthur; Machedon-Pisu Mihai; Machedon-Pisu Teodor (MDPI Coatings, 2024)
Grooving or gouging is a process of thermal processing of metals or welded semi-finished products. The gouging process is generally used to process the root of butt welds to remove possible welding defects. The possibility to obtain and characterize the surfaces after manual and mechanized plasma cutting in the field of bridges and viaducts from highways to construction sites in order to increase the quality of butt-welded joints is analyzed in this article. In order to mechanize the process, a linear universal displacement device for welding, cutting, or slitting that ensures the uniform movement of the torch was designed and executed herein. As a result, with the help of this device and the tests performed on a construction steel S355J2 after mechanized plasma cutting, the cut samples obtained facilitated the analysis of the macrostructure and microstructure of the thermally influenced zone and of the intermediate zone between the thermally influenced zone and the base material as well as their hardness. By mechanizing the cutting process, the productivity and quality of the surfaces obtained by this process has increased. The plasma gouging process is an ecological process and by mechanizing it, the manufacturing cost can be reduced.